The Chemistry of Ni–Sb Carbonyl Clusters – Synthesis and Characterization of the [Ni19Sb4(CO)26]4– Tetraanion and the Viologen Salts of [Ni13Sb2(CO)24]n– Carbonyl Clusters. Issue 25 (17th July 2014) - Femoni, Cristina; Iapalucci, Maria Carmela; Longoni, Giuliano; Zacchini, Stefano; Ciabatti, Iacopo; Della Valle, Raffaele Guido; Mazzani, Marcello; Riccò, Mauro
Abstract: Within the reinvestigation of Ni–Sb carbonyl cluster chemistry, we report here the synthesis and characterization of the new [Ni19 Sb4 (CO)26 ] 4– cluster and the synthesis, structure, magnetic characterization and electrical resistivity of the viologen salts of the previously known [Ni13 Sb2 (CO)24 ] n – ( n = 2, 3) anionic species. The crystal structures of [NEt4 ]4 [Ni19 Sb4 (CO)26 ], [EtV]8 [Ni13 Sb2 (CO)24 ]3 · 4DMF· 2C6 H14 and [EtV]3 [Ni13 Sb2 (CO)24 ]· 1.5THF (EtV = 1, 1′‐diethyl‐4, 4′‐bipyridilium cation, DMF = N, N ‐dimethylformamide, THF = tetrahydrofuran) are described. Notably, the unit cell of [EtV]8 [Ni13 Sb2 (CO)24 ]3 · 4DMF· 2C6 H14 involves a mixture of two [Ni13 Sb2 (CO)24 ] 3– trianions and one [Ni13 Sb2 (CO)24 ] 2– dianion, as it also contains eight [EtV] +· radical monocations, which are assembled in infinite stacks. In contrast, the unit cell of the [EtV]3 [Ni13 Sb2 (CO)24 ]· 1.5THF salt contains four [Ni13 Sb2 (CO)24 ] 3– trianions along with twelve [EtV] +· radical monocations, four of which are arranged into two pairs of isolated dimers, whereas the other two sets of four form two infinite stacks that extend over the whole crystal. The charges of the miscellaneous ions have been assigned on the basis of electroneutrality and spectroscopic evidence. More specifically, the infrared spectra of [EtV]8 [Ni13 Sb2 (CO)24 ]3 · 4DMF· 2C6 H14, both in the solid state and in solution, clearly indicate the presence of a 2:1 mixture of [Ni13 Sb2 (CO)24 ] 3– and [Ni13 Sb2 (CO)24 ] 2– anions. Resistivity measurements performed on pellets of powdered samples indicate that the [EtV]8 [Ni13 Sb2 (CO)24 ]3 · 4DMF· 2C6 H14 salt substantially behaves as an insulator. A study of the magnetic behaviour of [EtV]8 [Ni13 Sb2 (CO)24 ]3 · 4DMF· 2C6 H14 evidences pairing among the electrons of the EtV +· molecules, in agreement with DFT calculations, and the odd‐electron clusters behave as paramagnetic centres of spin S = 1. Abstract : The synthesis and characterization of the new [Ni19 Sb4 (CO)26 ] 4– cluster, as well as the synthesis, structure, magnetic characterization and electrical resistivity of the viologen salts of the previously known [Ni13 Sb2 (CO)24 ] n – ( n = 2, 3) anionic species are reported.